2006
DOI: 10.1007/s00428-006-0197-2
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial sleeves of pulmonary veins and atrial fibrillation: a postmortem histopathological study of 100 subjects

Abstract: Atrial fibrillation (AF) is triggered by ectopic beats originating from extensions of the left atrial myocardium over the pulmonary veins (PVs), so-called myocardial sleeves. A total of 100 hearts (393 PVs) obtained at autopsy were studied. Of these, 50 were from patients with chronic AF and 50 from controls in sinus rhythm. Out of a total of 393 PVs studied, a sleeve was present in 349 PVs (88.8%). The myocardial sleeves frequently harboured senile atrial amyloid and scarring. These two changes were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…This striated muscle compartment of pulmonary veins in humans is the subject of special clinical attention because it is the source of ectopic beats initiating atrial fibrillation [10][11][12][13]. Similar myocardial striated sleeves extending near heart chambers into the beginnings of main vessels were found in the aorta, pulmonary artery [14,15], and caval veins [16].…”
Section: Correspondencementioning
confidence: 97%
“…This striated muscle compartment of pulmonary veins in humans is the subject of special clinical attention because it is the source of ectopic beats initiating atrial fibrillation [10][11][12][13]. Similar myocardial striated sleeves extending near heart chambers into the beginnings of main vessels were found in the aorta, pulmonary artery [14,15], and caval veins [16].…”
Section: Correspondencementioning
confidence: 97%
“…Similar to that noted with fibrosis [4] and certain infiltrative disorders [5], amyloid deposition in the heart results in the interruption of normal cardiac impulse relay [6, 7] and may manifest as interatrial depolarization abnormalities [8]. Such abnormalities in turn are a purported arrhythmogenic substrate for atrial tachyarrhythmias, mainly atrial fibrillation [6, 7]. Using right atrial appendages that had been obtained from 245 patients undergoing open-heart surgery, Röcken et al [6] demonstrated that IAA significantly affected P wave duration and increased the risk of atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, myocytes in PV of AF patients were not uniform and surrounded by fibrous tissues compared with those in controls. Moreover, Steiner et al (2006) reported that amyloid deposition and scarring in myocardial sleeves t e n d e d t o b e o b s e r v e d m o r e f r e q u e n t l y i n AF patients relative to control patients. Interestingly, the incidence of atrial myocardium extending beyond the PV-LA junction up to the PV periphery in all the examined PV specimens is commonly reported to be 88 to 89% (Tagawa et al, 2001;Steiner et al, 2006).…”
Section: Myocardial Sleeves In Pvmentioning
confidence: 99%